Electrochemical Determination of Tramadol in Ampoule Dosage Forms by Cyclic Voltammetry - KUCUK†, AYSEL; KADIOGLU*, YUCEL; EKINCI‡, DUYGU (Asian Journal of Chemistry, 2024)
A voltammetric study was performed to examine the electroactive behaviour of tramadol hydrochloride. Tramadol was analyzed with cyclic voltammetry (CV) method in the concentration range 10-100 μg/mL (0.0336-0.33 mM) with a detection limit 5 μg/mL (0.0168 mM). The developed and validated method was successfully applied to the analysis of commercial ampoules. Recovery values were between 89 and 92 %. Developed electroanalytical method in this study was accurate, sensitive, precise and reproducible and could be directly and easily applied to pharmaceutical forms. Besides, the statistical results were compared with that of the data obtained from previous UV study. The reaction mechanism of this compound using cyclic voltammetric measurements at different scan rates was also tried to be explained by the electrochemical behaviour of tramadol.